ANALISIS PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUTUSAN PELANGGAN PADA STUDIO FOTO FOTOKITA - Putri, Rani Budianawati; Andayani, Sri; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2016)
Marketing activity is important for the company, because each company are required to determine the right marketing strategy in order to grab consumers amid competition is increasingly competitive. One of the factors that determine the customer's decision is the quality of services that focuses on five dimensions: physical evidence (tangibles), reliability (reliability), responsiveness (responsive), assurance (assurance), attention (empathy). This study aims to determine whether there is influence between the Quality of Service which consists of five dimensions: Tangible, Reliability, Responsive, Assurance, and Empathy to the Decision of Customer Services Photo Studio FotoKita, and to determine the indicators are of the dimensions of Quality of Service of the most dominant and influential on Customer decisions on Services Studio Photos Kita.This research is a survey. The population in this study are all Customers who already use photos and photo printing services in these studios as many as 100 people were taken by using non-probability sampling decision. Data analysis technique used in this research is multiple linear analysis techniques.The results in this study show that: (1) tangibles, responsiveness, reliability, assurance, and empathy significantly influence the customer's decision; (2) physical form (tangibles) has a dominant influence on customer decisions.